Comparing line transect and grid sampling designs to quantify species richness, abundance, diversity and similarity of non-volant small mammals in Gunung Gading National Park, Sarawak, Borneo - Mathew, Jenang (Universiti Malaysia Sarawak (UNIMAS), 2015)
Species richness, diversity, similarity and shared species are basic measurements that are needed in quantifying abundances of animal in their natural habitat. Specifically, species richness, species diversity, species similarity and shared species of non-volant small mammal abundances in Gunung Gading National Park is reported here by comparing line transect and grid sampling which were conducted with ten sampling occasions within January 2012 to December 2012. A total of 19 species were captured in line transect and 14 species were captured from grid with 396 and 295 number of individuals respectively. Five families represented by four orders, which comprises of 691 individuals were observed in total. Shannon index for line transect was slightly higher than for grid sampling with value of 2.48 and 2.13, respectively. Diversity t test also concludes that there is a significant difference between line transect and grid, thus, the null hypothesis is rejected. Program EstimateS Version 9.1.0 (Colwell, 2013) was used to evaluate ACE, Chao1 and Jack1 species richness with our data sets. For line transect arrangement, estimated about 20 to 23 species are to be expected while for grid sampling, an estimated 15 to 16 species of non-volant small mammals are to be expected. This means that both study designs have at least average of two unseen species during these ten sampling occasions. Morisita similarity index estimated that transect and grid were 92% similar in terms of species.